Pozycja ustrojowa wojewodów i starostów jako przedstawicieli rządu w latach 1919–1928 - Gałędek, Michał (Studia Iuridica Toruniensia, 2013)
The article presents an important aspect in the history of the evolution of legal status of voivode’s and starost’s as the off ices representing local government administration in the interwar period. Although they were responsible for the whole administration in the province, they had under their control only some branches of administration. At the begining neither voivodes in the voivodeships nor starosts in the counties did not have any legal impact on the off ices which were not placed under their supervision. This article presents how this situation was gradually changing equipping government representatives with the tools to enable them to infl uence on the independent local authorities. The fi nal turning point of publication is the moment of coming into force the presidental decree of 19 January 19 1928 concerning the organization and operation of general administration, which ended the fi rst phase of work on the construction of the administration system of the Republic of Poland in the interwar period. This publication has been prepared based on the sources of universally binding law and the the government acts. The analisys of legal issues was made using formal-dogmatic based on administration law literature, especially of the interwar period.